Nollywood Stars : Media and Migration in West Africa and the Diaspora - Tsika, Noah, 1983- (Book collections on Project MUSE., 2015)
"In this comprehensive study of Nollywood stardom around the world, Noah A. Tsika explores how the industry's top on-screen talents have helped Nollywood to expand beyond West Africa and into the diaspora to become one of the globe's most prolific and diverse media producers. Carrying VHS tapes and DVDs onto airplanes and publicizing new methods of film distribution, the stars are active agents in the global circulation of Nollywood film. From Omotola Jalade-Ekeinde's cameo role on VH1's popular series Hit the Floor to Oge Okoye's startling impersonation of Lady Gaga, this book follows Nollywood stars from Lagos to London, Ouagadougou, Cannes, Paris, Porto-Novo, Sekondi-Takoradi, Dakar, Accra, Atlanta, Houston, New York, and Los Angeles. Tsika tracks their efforts to integrate into various entertainment cultures, but never to the point of effacing their African roots"--The publisher.